A novel way to understand plant species preferences in relation to groundwater discharge conditions using a trait‐based approach. Issue 4 (14th July 2015) - van der Knaap, Yasmijn A. M.; Douma, Jacob C.; Aerts, Rien; van Ek, Remco; van Bodegom, Peter M.
Abstract: Groundwater discharge sites harbour characteristic and often rare plant communities that differ substantially from groundwater recharge sites. It is not known which abiotic conditions at these sites drive the differences in community composition. A trait‐based approach, which relates species traits to abiotic conditions, may provide insight in this relationship and improve conservation management of these characteristic communities. We used this approach to identify the following: (i) dominant abiotic conditions that shape plant communities at discharge sites and (ii) characteristic traits associated with these abiotic conditions. First, we performed a (qualitative) literature survey to relate plant traits to various abiotic conditions at discharge sites. Second, we performed a meta‐analysis to quantitatively test the trait selection at discharge sites. For the meta‐analysis, we compiled a species discharge preference database ( n = 170), based on literature and field data. We performed linear regression to relate traits to species discharge preference. Only 5 out of the 11 traits tested (low leaf phosphorus content, high leaf N:P, low rate of clonal reproduction, low maximum height and high seed mass) were significantly related to discharge preference, while the explained variance was low ( R 2 < 0.09). Our results suggest the following: (i) Despite the inclusion of traits specifically related to prevailing local environmental conditions, beyond commonly applied traits, hardly any differences were revealed; this indicates a need for more comprehensive eco‐physiological understanding (and information on the selection of combinations of traits). (ii) A trait‐based approach may not be highly distinctive in environments differing in only a few specific characteristics. Copyright © 2015 John Wiley & Sons, Ltd.